Teaching the Physical Exam and Psychomotor Skills in the Clinical Setting - Julie Damp; Thomas Morrison; Charlene Dewey; Lisa Mendes (Association of American Medical Colleges, 2015)
Abstract The physical exam is a useful diagnostic tool in clinical care. Teaching physical diagnosis has been shown to improve students' skills. Clinical teaching faculty, however, may experience discomfort with incorporating teaching into their busy daily routine. Time constraints and lack of formal training on effective teaching are among the reasons for this. This workshop was developed to equip faculty with tools to more effectively teach physical diagnosis and psychomotor skills in the clinical setting. The workshop utilizes old and new technology and adult learning principles to allow practice of these skills in a safe learning environment. The interactive learning activities are novel methods of simulating the targeted skills (auscultation simulated with differentiating owl calls, psychomotor skills simulated with origami). The workshop can be implemented in a short-enough time to be incorporated into the workflow of busy clinicians, addressing the time barrier in participating. The provided tools decrease the resources needed to provide faculty development in this area. We have given this workshop to approximately 40 faculty in cardiology, internal medicine, and pediatrics. Attendance was voluntary. The workshop as well received with, an average overall rating of 4.23 out of 5. Particular positive aspects of the workshop highlighted by the faculty participants included that it was very interactive, addressed needed skills, and was hands-on. Participants' self-assessment of comfort with the skills taught was an average of 2.70 out of 5 prior to and 4.40 out of 5 after the workshop. On follow-up survey, a majority of responding faculty reported implementing these skills in their teaching.